Cadmium toxicity in medicinal plants: An overview of the tolerance strategies, biotechnological and omics approaches to alleviate metal stress - Al-Khayri, Jameel M.; Banadka, Akshatha; Rashmi, R; Nagella, Praveen; Alessa, Fatima M.; Almaghasla, Mustafa I. (Frontiers in Plant Science, 2023)
Medicinal plants, an important source of herbal medicine, are gaining more demand with the growing human needs in recent times. However, these medicinal plants have been recognized as one of the possible sources of heavy metal toxicity in humans as these medicinal plants are exposed to cadmium-rich soil and water because of extensive industrial and agricultural operations. Cadmium (Cd) is an extremely hazardous metal that has a deleterious impact on plant development and productivity. These plants uptake Cd by symplastic, apoplastic, or via specialized transporters such as HMA, MTPs, NRAMP, ZIP, and ZRT-IRT-like proteins. Cd exerts its effect by producing reactive oxygen species (ROS) and interfere with a range of metabolic and physiological pathways. Studies have shown that it has detrimental effects on various plant growth stages like germination, vegetative and reproductive stages by analyzing the anatomical, morphological and biochemical changes (changes in photosynthetic machinery and membrane permeability). Also, plants respond to Cd toxicity by using various enzymatic and non-enzymatic antioxidant systems. Furthermore, the ROS generated due to the heavy metal stress alters the genes that are actively involved in signal transduction. Thus, the biosynthetic pathway of the important secondary metabolite is altered thereby affecting the synthesis of secondary metabolites either by enhancing or suppressing the metabolite production. The present review discusses the abundance of Cd and its incorporation, accumulation and translocation by plants, phytotoxic implications, and morphological, physiological, biochemical and molecular responses of medicinal plants to Cd toxicity. It explains the Cd detoxification mechanisms exhibited by the medicinal plants and further discusses the omics and biotechnological strategies such as genetic engineering and gene editing CRISPR- Cas 9 approach to ameliorate the Cd stress.